Emerging role of exosomal microRNA in liver cancer in the era of precision medicine; potential and challenges - El Hayek, Tarek; Alnaser-Almusa, Osama Abdulwahab; Alsalameh, Sulaiman Mamoun; Alhalabi, Maya Taofik; Sabbah, Ahmad Nedal; Alshehri, Eman Abdullah; Mir, Tanveer Ahmad; Mani, Naresh Kumar; Al-Kattan, Khaled; Chinnappan, Raja; Yaqinuddin, Ahmed (Frontiers in Molecular Biosciences, 2024)
Exosomal microRNAs (miRNAs) have great potential in the fight against hepatocellular carcinoma (HCC), the fourth most common cause of cancer-related death worldwide. In this study, we explored the various applications of these small molecules while analyzing their complex roles in tumor development, metastasis, and changes in the tumor microenvironment. We also discussed the complex interactions that exist between exosomal miRNAs and other non-coding RNAs such as circular RNAs, and show how these interactions coordinate important biochemical pathways that propel the development of HCC. The possibility of targeting exosomal miRNAs for therapeutic intervention is paramount, even beyond their mechanistic significance. We also highlighted their growing potential as cutting-edge biomarkers that could lead to tailored treatment plans by enabling early identification, precise prognosis, and real-time treatment response monitoring. This thorough analysis revealed an intricate network of exosomal miRNAs lead to HCC progression. Finally, strategies for purification and isolation of exosomes and advanced biosensing techniques for detection of exosomal miRNAs are also discussed. Overall, this comprehensive review sheds light on the complex web of exosomal miRNAs in HCC, offering valuable insights for future advancements in diagnosis, prognosis, and ultimately, improved outcomes for patients battling this deadly disease.